Periclimenoides tyrannodentatus, a new species of symbiotic shrimps (Crustacea: Decapoda: Palaemonidae) from Taiwan - Šobáňová, Anna; Lin, Chia-Wei; Ďuriš, Zdeněk (Zootaxa, 2017)
A new species of sponge-endosymbiotic shrimps, Periclimenoides tyrannodentatus, is described and illustrated. The species is remarkable for its stout subspatulate first pereiopods chelae with lateral fan-shaped pectination on their dactyli. Due to this character and simple ambulatory dactyli, the new species is similar to the type species of the genus, P. odontodactylus. Another remarkable character is in the unique shape of the minor chela of the second pereiopods; the distal cutting edges of its compressed fingers are distinctly expanded and armed with quite impressive dentitions. An identification key to the three currently recognised species of the genus Periclimenoides is provided. The new species represents the first record of the genus Periclimenoides from Taiwan.